THE USE OF GOOGLE TRANSLATE in WRITING EXPLANATION TEXT BY XI GRADE STUDENTS OF SMA N 1 AIR PUTIH - Yosephin Elisabet Sembiring; Anni Holila Pulungan (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
This study deals with the usage of Google Translate (GT) in writing explanationtext by XI Grade Students of SMA N 1 Air Putih. The objectives of this studywere to explain the use of GT in writing explanation text by XI grade students ofSMA N 1 Air Putih and to describe the teacher’s reason in using GT as a media inwriting explanation text. This research was conducted by using descripstivequalitative. The data were gathered by interviewing and distributingquestionnaires to the teacher and the students. The usage of GT in writingexplanation text mostly gave positive responses from both teacher and students.GT was simplest, time-saving, accessible and helpful. The interview andquestionnaire results showed the most students answered GT was quite interesting(50%) and very interesting (39%), then not really (11%). Then, the data showedthat the students agree that GT was simplest way and saved their time (50%), thensome of them answered that it was quite simplest and time-saving (42%), and notreally simplest and time-saving (8%). Most of students answered that GT wasextremely helpful (45%), some of them felt that it was adequate helpful (39%),then some of them thought it was not really helpful (8%). The teacher use GT as alearning-media. She thought it can help the students to found a new vocabularyand stimulated the students more productive. She wanted to gave the studentsopportunity in utilized and enjoyed the technology during learning.